2016
DOI: 10.4172/2161-0940.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physical Growth and Weight Patterns of Egyptian Children with Phenylketonuria under a Phenylalanine-Restricted Diet

Abstract: Objective: A phenylalanine-restricted diet is the mainstay of phenylketonuria (PKU) treatment but does not normally provide enough protein for growth requirements. We evaluated the effect of a phenylalanine-restricted diet on growth parameters of Egyptian children with PKU.Methods: Twenty-eight PKU children were evaluated for weight, height, and body mass index (BMI) and were compared with matched controls at baseline and then their baseline parameters were compared with those collected 2 years later.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The nutritional, biochemical and clinical follow-up of persons with PKU requires inspection of the body mass index, nutrient deficiency signs, intake of nutrients and biomarkers [13]. Zaky et al [14] reported that early diagnosis of phenylketonuria and the use of a Phe-restricted diet lead to avoiding growth problems. A Pherestricted diet is a phenylalanine-free amino acid containing formula enriched with minerals, vitamins, fatty acids and tyrosine [15].…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional, biochemical and clinical follow-up of persons with PKU requires inspection of the body mass index, nutrient deficiency signs, intake of nutrients and biomarkers [13]. Zaky et al [14] reported that early diagnosis of phenylketonuria and the use of a Phe-restricted diet lead to avoiding growth problems. A Pherestricted diet is a phenylalanine-free amino acid containing formula enriched with minerals, vitamins, fatty acids and tyrosine [15].…”
Section: Introductionmentioning
confidence: 99%